Abundance - Klein, Ezra, 1984-; Thompson, Derek, 1986- (New York : Avid Reader Press, 2025)
"Abundance is a once-in-a-generation, paradigm-shifting call to rethink big, entrenched problems that seem mired in systemic scarcity: from climate change to housing, education to healthcare"--
Includes bibliographical references (pages 227-272) and index.